Revealing transient structures of nucleosomes as DNA unwinds. Issue 13 (2nd July 2014) - Chen, Yujie; Tokuda, Joshua M.; Topping, Traci; Sutton, Julie L.; Meisburger, Steve P.; Pabit, Suzette A.; Gloss, Lisa M.; Pollack, Lois
Abstract: The modulation of DNA accessibility by nucleosomes is a fundamental mechanism of gene regulation in eukaryotes. The nucleosome core particle (NCP) consists of 147 bp of DNA wrapped around a symmetric octamer of histone proteins. The dynamics of DNA packaging and unpackaging from the NCP affect all DNA-based chemistries, but depend on many factors, including DNA positioning sequence, histone variants and modifications. Although the structure of the intact NCP has been studied by crystallography at atomic resolution, little is known about the structures of the partially unwrapped, transient intermediates relevant to nucleosome dynamics in processes such as transcription, DNA replication and repair. We apply a new experimental approach combining contrast variation with time-resolved small angle X-ray scattering (TR-SAXS) to determine transient structures of protein and DNA constituents of NCPs during salt-induced disassembly. We measure the structures of unwrapping DNA and monitor protein dissociation from Xenopus laevis histones reconstituted with two model NCP positioning constructs: the Widom 601 sequence and the sea urchin 5S ribosomal gene. Both constructs reveal asymmetric release of DNA from disrupted histone cores, but display different patterns of protein dissociation. These kinetic intermediates may be biologically important substrates for gene regulation.